THE EFFECTIVENESS OF USING SERIES OF PICTURES AS MEDIA TO IMPROVE THE STUDENTS’ SPEAKING ABILITY AT STORYTELLING: A CASE OF THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 2 PURWODADI - M. Khoiruddin (Universitas PGRI Semarang, 2014)
The objectives of this research are (1) to find out the speaking ability of SMA Negeri 2 Rembang students before being taught using series pictures of storytelling, (2) to find out the speaking ability of SMA Negeri 2 Purwodadi students after being taught using series pictures of storytelling, and (3) to find out whether or not there is a significant difference of speaking ability of SMA Negeri 2 Purwodadi students before and after being taught using series pictures of storytelling.This study uses Experimental method. The number of populations in this research is30 students. The method of data collection is spoken test. First the writer gives pre-test to the students and scores. Second the writer gives a treatment for two meetings at this time, the writer implements the series pictures in classroom activities. At last, the writer gives the students a post test. The data analysis reveals that the mean of pre-test score is 61,03 ; it is at fair level. The mean of post-test score is 76,1 ; it is at good level. Then the result of t-test is9,71, and the t-table of 30 students is2,04. The result of t-test is higher than t-table. Based on research analysis, the writer takes conclusions: first the speaking ability of the students before being taught using series pictures of storytelling is fair, second the speaking ability of the students after being taught using series pictures of storytelling is good, and last there is significant improvement of English speaking ability of the students taught by using series pictures of storytelling. The writer also suggests to all of teachers of senior high school. It is better for them to use the media of series pictures of storytelling to improve the students’ speaking ability. It is for the simple reason that a series pictures are a media to improve the speaking ability at storytelling. The writer also suggests to the students that the study is as recommendation to motivate the students in improving the students’ speaking ability. The students are encouraged to give their opinions, ideas and imagination about the presented pictures. Definition of key terms (1) series picture A picture is an illustration of pictures that can be used as a two dimensional visual representation of percent, place, or things. (2) Media is any extension of man which allows him to affect other people who are not in face to face with him. (3) Story telling is In this research storytelling is used to improve the students’ speaking ability. It caused that storytelling can improve the ideas and imagines their story and express it by telling the story. It helps the students to speak and talk active.